Antimicrobial and Antioxidant Activities of Hornstedtia leonurus Retz. Extracts - Jani, Nor Akmalazura; Ibrahim, Nordiana; Hashim, Siti Ernieyanti; Mohd. Sirat, Hasnah (Journal of Science and Technology, 2016)
The n-hexane, ethyl acetate and methanol extracts of the rhizome, leaf and stem of Hornstedtia leonurus Retz. from Malaysia were tested for antimicrobial and antioxidant activities. Antimicrobial activities were screened against three bacteria and two fungi by the broth microdilution assay, while antioxidant activities were analysed using DPPH radical scavenging assay. Most of the extracts exhibited weak to moderate antimicrobial activities (MIC 900 – 1800 µg/mL) except ethyl acetate extract of the rhizome with strong activity against Candida albicans (MIC 225 µg/mL) and Aspergillus niger (MIC 450 µg/mL) as well as methanol extract of the rhizome that inhibited activity of Staphylococcus aureus with MIC value of 450 µg/mL. Among nine extracts tested, n-hexane extract of the rhizome possessed moderate free radical scavenging activity with IC50 value of 59.60 ± 0.69 µg/mL compared to vitamin C (IC50 = 21.21 ± 1.25 µg/mL).